Towards an Understanding the Role of Seals in the Subneolithic Communities of the South-East Coast of the Baltic Sea. The Bacula from Šventoji 3 Site - Osipowicz, Grzegorz (Archaeologia Lituana, 2020)
The article presents the results of traceological studies of two harp seal bacula, from the Šventoji 3 site (coastal Lithuania). As a result of the microscopic observations carried out, technological and functional microtraces were discovered on both artefacts. The analysis of the use-wear traces, which are better readable only on one of the artefacts, allowed for a hypothesis that they arose as a result of contact with well-tanned and dry hide. This made it possible to assign to the studied artefacts the function of objects of everyday use, having direct contact with this material. The findings were illustrated with the current knowledge on the use of bacula in prehistory, historical times and among archaic communities known from ethnographic observations.
Keywords: traceology; seal; penis bone; baculum; hide; Subneolithic; Lithuania